Influence of Advertising Appeals on Buying Behaviour with Reference to Cosmetic Brands - Ganjoo, Maithili (International Journal of Psychosocial Rehabilitation, 2020)
Advertising plays an important role in influencing the consumers purchase decisions. By using different advertising appeals, the brands are able to both create awareness about their products, as well as build perceptions around them that touch the consumer’s heart or reason. Awareness and perception go hand in hand forming purchase intent, leading to the final purchase. This is true of advertising for cosmetic brands that is one of the fastest growing market in India. Glossy print ads, celebrity endorsement, sex-appeal, humor and online influencers are some of the advertising appeals used to create awareness and build perceptions around the brands. This particular research aimed to find out how these advertising appeals influence the buying behavior of the residents of Delhi-NCR. The study found that while the advertising appeals has been successful in creating awareness and changing attitude towards cosmetics consumption among the respondents, but building brand perception is a more complex process which requires time, trust and technology.